THE REINFORCEMENTS OF LANGUAGE DEFICIT IN AUTISTIC CHILD THROUGH APPLIED BEHAVIOR ANALYSIS (ABA) METHOD - MILASARI, FAIKATUL (LANGUAGE HORIZON, 2019)
Abstract In recent decades the number of people diagnosed as autism has increased massively to an estimated number of 1 in 100. In Indonesia itself the number of autistic children has increased every year. However, the curing of children with autism is still relatively low, especially the autistic people who live in villages (inland) of Indonesia since the low education in that area. That?s why the parents need more understanding about how to treat their autistic children to develop their language deficit like other normal children. This study would discuss the reinforcements of language deficit in autistic child that was done through applied behavior analysis (ABA) method. It occurred to Dylan, an autistic child of 3 years old in which his language developed more slowly than others and need some language reinforcements through ABA method to communicate with others.The primary of this study is two questions; (1) What are the categories of verbal operant in Dylan?s language development in using ABA method? (2) How does Dylans language developmental result in using ABA method? To finish this study, the method applied was mix method which is descriptive qualitative used to answer RQ 1 with documentation technique since it is in the form of videos while quantitative to answer RQ 2 with Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP) by Sundberg. In this study, the theory of Verbal Behavior using verbal operant by Skinner of language development in psycholinguistics point of view was applied to analyze the data. The finding showed that among video 1 (V1) to video 4 (V4) data some categories of verbal operant (VO) were used as positive reinforcements there were mand, echoic, tact, intraverbal and other category which did not exist in the verbal operant but the researcher categorized it as ?gestural? and ?verbal tact? as new categories. Thus, through VB-MAPP Milestones result it can be seen that Dylan?s verbal behavior got development and he was able to maintain what he had learned before. However, the total transition scores of VB-MAPP milestones form, barriers form and negative behavior and instructional control among all of videos data were average 1 it meant Dylan still had to practice more and learned some categories such as textual and transcriptions which were not applied yet to acquire the skills needed for studying in a less restrictive educational environment. Keywords: Autism, Verbal Operant (VO), Applied Behavior Analysis (ABA), Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP)